Tuberculin Skin Test and Quantiferon®-TB Gold In-Tube Test for Latent Tuberculosis Before Biologic Treatments: Lower Agreement Rate in Spondyloarthropathies Compared to Rheumatoid Arthritis - Ilgen, Ufuk; Turan, Sezin; Emmungil, Hakan; Sari, Alper; Erden, Abdulsamet; Kilic, Levent; Kalyoncu, Umut (Wiley, 2019)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology/Association-of-Rheumatology-Professionals (ACR/ARP) -- NOV 08-13, 2019 -- Atlanta, GA